2004
DOI: 10.1177/0145445503258995
|View full text |Cite
|
Sign up to set email alerts
|

A Modification of the Token Economy for Nonresponsive Youth in Family-Style Residential Care

Abstract: Out-of-home treatment for youth with conduct problems is increasing rapidly in this country. Most programs for these youth deliver treatment in a group format and commonly employ some version of a token economy. Despite widespread evidence of effectiveness, a substantial minority of treated youth fail to respond. Participants for this study were 3 youth who were nonresponsive to treatment provided in a family-style residential care program with a comprehensive token economy. Our approach to the "nonresponse" o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Previous research and theory have shown that performance feedback can result in improved accuracy of time estimation [Ryan and Robey, 2002]. The use of feedback mechanisms for treatment intervention is supported by other studies that have demonstrated the effectiveness of reward-contingent behavioral feedback therapies in youth with aggressive symptoms who were otherwise treatment resistant [Field et al, 2004].…”
Section: Discussionmentioning
confidence: 81%
“…Previous research and theory have shown that performance feedback can result in improved accuracy of time estimation [Ryan and Robey, 2002]. The use of feedback mechanisms for treatment intervention is supported by other studies that have demonstrated the effectiveness of reward-contingent behavioral feedback therapies in youth with aggressive symptoms who were otherwise treatment resistant [Field et al, 2004].…”
Section: Discussionmentioning
confidence: 81%
“…Fabiano et al reported that the economy token “assigns points for targeted behaviors within the program setting,” and the technique is widely used in programs treating dysfunctional behaviors of various disorders (21, 22, 31, 33). However, most studies specifically comparing token economy technique effects have used counts of behaviors emitted as outcome measures, then comparing average frequencies at baseline date and post-intervention (21, 22, 31, 33).…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies specifically comparing token economy technique effects have used counts of behaviors emitted as outcome measures, then comparing average frequencies at baseline date and post-intervention (21, 22, 31, 33). Other studies comparing effects of behavioral intervention have used standardized measures from cognitive tasks or behavioral inventories (1416, 23, 24, 27, 28, 30).…”
Section: Introductionmentioning
confidence: 99%
“…Teaching-Family research on aggression suggests that Teaching-Family procedures effectively reduced the aggression displayed by group home youth (Field et al 2004b;Phillips 1968), parent/caregiver perceptions of aggressive behaviors displayed by group home youth (Larzelere et al 2001) and the frequency of crisis teaching episodes in reaction to severe behaviors such as aggression (Field et al 2004a). Teaching-Family procedures reduced staff use of restraint (Jones and Timbers 2003), the number of days spent in inpatient care by youth for whom aggression was a referring factor (Fabry et al 2002) and disruptive behaviors, including aggression, displayed by an adult with intellectual disabilities living in a group-home (Reese et al 1998).…”
Section: Evidence Basementioning
confidence: 99%